2020
DOI: 10.1038/s41598-020-71054-2
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual indocyanine green films for non-invasive swallowing assessment and inflammation detection through NIR/SWIR optical imaging

Abstract: Indocyanine green (ICG) is the most commonly used FDA-approved agent for clinical optical imaging, administered through injections only, due to its poor membrane permeability. Although ICG has vast potential for non-invasive non-radioactive imaging in patients, the clinical applications are limited by the invasive administration and short half-life in blood circulation. To expand the clinical value of ICG, non-toxic chitosan-based ICG-loaded films were designed for sublingual administration for near-infrared (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…ICG, a dye already approved for intravenous use in children, adolescents, and adults, has already shown broad applications in preclinical [22][23][24] and clinical studies. [25,26] Similarly to the current study, Morscher et al demonstrated its oral use for imaging gastric emptying in mice.…”
Section: Discussionmentioning
confidence: 99%
“…ICG, a dye already approved for intravenous use in children, adolescents, and adults, has already shown broad applications in preclinical [22][23][24] and clinical studies. [25,26] Similarly to the current study, Morscher et al demonstrated its oral use for imaging gastric emptying in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For ICG-based medical imaging, oral administration of ICG dye is not commonly used, 50 because if ICG is administered orally, it would be absorbed in the digestive system, and would cost about 1 h to reach the systemic circulation in the mouse model. 50 Most ICG dye would access the hepatic portal system and be carried to the liver by portal vein, 51 and the liver would extract over 70% of ICG dye in healthy humans. 52 , 53 Therefore, a high ICG dose with the OA method would have more ICG dye absorbed by the digestive system, and more ICG dye could enter the systemic circulation and reach dental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…124 Similarly, an attempt was made to increase the clinical utility of ICG via tabletized nanomedicine by developing chitosan-based ICG films. 123 These mold-casted sublingual formulations were obtained with two different release patterns (80% in 4 or 25 h) and offering enhanced systemic absorption and circulation of ICG. These films allow quick detection of inflammation in mouse model.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In addition to the use of nanomedicine in tabletized form, it is interesting to employ tabletized formulation(s) for oligonucleotides and imaging agents’ delivery. , For example, siRNA lipoplexes were prepared in the form of a tablet . The dried form of siRNA lipoplex was able to increase the stability of siRNA while maintaining over 60% of the gene-silencing capacity.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%